Synthesis and Characterization of Benzodithiophene (BDT) Quinoid Compounds as a Potential Compound for n-Type Organic Thin-Film Transistors (OTFT) - Mokhamat Ariefin; Vety Sri Harlinda Ayudha (Jurnal Kimia Sains dan Aplikasi, 2020)
Two potential compounds as an n-Type organic thin-film transistor (OTFT) from benzodithiophene (BDT) derivatives have been synthesized and characterized. BDT was chosen as the core because it has π-conjugated bonds, rigid structures, and planar. Quinoid structure with end-cap (terminal group) in the form of dicyanomethylene is used because it can lower the LUMO value of the compound, and side chains are selected in the form of alkoxy so that two BDT derivatives are obtained namely BDTQ-6 (hexyloxy) and BDTQ-10 (decyloxy). Based on the results of TGA, BDTQ-6 and BDTQ-10 have decomposition points of 183°C and 203°C, which indicate the compound has excellent thermal stability. From the UV-Vis measurement, the λmax value of the two compounds is 599 nm with optical gap energy (Eg°pt) of 1.7 eV. From the DPV measurement, the LUMO value for the two compounds is -4.3 eV, with an energy gap (Eg) of 1.69 eV (BDTQ-6) and 1.70 eV (BDTQ-10). Based on observations of the crystal structure through x-ray diffraction, it was found that the BDTQ-10 crystal has a "brick type" layer arrangement with a distance between layers of 3.55 Å. With excellent thermal stability and suitable LUMO values and energy gaps, it is expected that BDTQ-6 and BDTQ-10 compounds have the potential to be n-Type OTFT materials.